ÇOCUKLARDA ASEMPTOMATİK KURŞUN ZEHİRLENMESİ - YAPICI, Gülçin; CAN, Günay; ŞAHİN, Ümit (Cerrahpaşa Medical Journal, 2014)
Background.- Environmental pollution problems threaten the nature and human health in the industrialized world. Lead which is a easy-processed and widespread metal, is used in general industrial production. Thus, the lead exposure is an important public health problem in most of developing and industrialized countries. In this review, we investigated the effects of lead exposure on children. Epidemiological researches which are about asymptomatic lead toxicity in children have been investigated by a literature screening. Disorders which are caused by lead exposure in children are seen as asymptomatic lead toxicity and can be diagnosed by screening tests. Epidemiological researches show that the lead accumulates in time even with low level exposure. Irreversible health effects are seen at exposure in the first 2 years of life-especially around 2 years of age and appear with symptoms like IQ deficits, behavior disorders, learning difficulty, hearing loss a later age. Lead toxicity in children is accepted as preventable public health problem in the developed countries and the prevalence of asymptomatic lead toxicity is 6-15%. In USA, screening of children at 6 months - 6 years age group is obligatory.